The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.pharmthera.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 1: A potential anti-inflammatory pathway in obesity-related asthma

Abstract: Alterations in arginine metabolism and accelerated formation of advanced glycation end-products (AGEs), crucial mechanisms in obesity-related asthma, can be modulated by glucagon-like peptide 1 (GLP-1). L-arginine dysregulation in obesity promotes inflammation and bronchoconstriction. Prolonged hyperglycemia, dyslipidemia, and oxidative stress leads to production of AGEs, that bind to their receptor (RAGE) further potentiating inflammation. By binding to its widely distributed receptor, GLP-1 blunts the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Another class of insulin secretagogue, glucagon-like peptide-1 analogues, also display promising antiinflammatory effects in mouse models, 23 and have recently been proposed as potential novel treatments for obesity-associated asthma. 24 Our findings relating to insulin are consistent with those of Chen et al 7 who observed an increased risk of asthma in patients with diabetes who are regularly prescribed insulin compared with matched controls (OR 2.23, 1.52-3.58). Previous work by this group has yielded similar results.…”
Section: Univariate Hr Estimates (95% Ci)supporting
confidence: 92%
See 1 more Smart Citation
“…Another class of insulin secretagogue, glucagon-like peptide-1 analogues, also display promising antiinflammatory effects in mouse models, 23 and have recently been proposed as potential novel treatments for obesity-associated asthma. 24 Our findings relating to insulin are consistent with those of Chen et al 7 who observed an increased risk of asthma in patients with diabetes who are regularly prescribed insulin compared with matched controls (OR 2.23, 1.52-3.58). Previous work by this group has yielded similar results.…”
Section: Univariate Hr Estimates (95% Ci)supporting
confidence: 92%
“…Our findings here may potentially demonstrate the difference between exogenous and endogenous insulin on the incidence risk of asthma, when considered alongside our results from insulin users. Another class of insulin secretagogue, glucagon‐like peptide‐1 analogues, also display promising antiinflammatory effects in mouse models, and have recently been proposed as potential novel treatments for obesity‐associated asthma …”
Section: Discussionmentioning
confidence: 99%
“…[122] In addition, GLP-1 binds to RAGE and inhibits RAGE activation. [123] GLP-1 is also reported to inhibit AGEs-induced apoptosis of EC cells, increase the ratio of antiapoptosis Bcl-2/pro-apotosis Bax, downregulate cytochrome C levels, and inhibit caspase-3 and caspase-9 activities. [124] Moreover, recent studies have shown that GLP-1 can directly act on GLP-1R of ECs, which may play a role in anti-AGEs by reducing RAGE expression.…”
Section: Glp-1 Receptor Agonistmentioning
confidence: 98%
“…IL-17 is able to improve the secretion of inflammatory cytokines such as IL-6, TNF- α , IL-8, CAM-1, and CM-CSF through the MAPK or NF- κ B pathway [ 56 ]. The association between obesity and neutrophil count in sputum is significant; in addition, a recent cluster analysis has shown that the presence of obesity-related asthma is characterized by increased airway neutrophils [ 57 59 ]. In addition to this, IL-17, IL-6, and TNF- α secreted by Th17 cells recruit and activate neutrophils in the lungs [ 60 ].…”
Section: Obesity and Asthmamentioning
confidence: 99%